ANALISA FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MATERI PENDIDIKAN KESEHATAN REPRODUKSI PADA SISWA SEKOLAH DASAR DI KECAMATAN SEMARANG TIMUR KOTA SEMARANG - widyah setiyowati (Universitas Muhammadiyah Semarang, 2019)
AbstracReproductive health education is part of health education which is essentially a form of intervention to create behaviors that are conducive to health. This will work well if done in an organized environment such as the school environment. Schools are a place to learn most teenagers are ideal places to provide health education, especially adolescent reproductive health. School-based reproductive health education is one of the most important and broad ways to help adolescents recognize and avoid risks related to reproductive health and increase knowledge about reproductive health. This study aims to determine the relationship of attitudes, perceptions and support of principals to the behavior of teachers in the provision of reproductive health education materials for elementary school students in the East Semarang sub-district of Semarang City. This research was included in an explanatory research study that explained the relationship between independent variables and dependent variables through hypothesis testing that had been formulated. The method used in this study is a survey method using cross sectional approach, where the independent variables and dependent variables are examined simultaneously. The number of samples is 34 respondents, data analysis uses chi square. The results of this study indicate there is a relationship between perceptions, attitudes and support of school principals with the behavior of giving reproductive health education materials to elementary school students in East Semarang Subdistrict, Semarang City based on the results of Sig ≤0,05 so Ho is rejected. Suggestions in this study are for teachers, educational institutions, health workers and the community to support the provision of reproductive health education in accordance with the age of children. Keywords: Factors, Reproductive Health Education